Creating Policy Space : Responsive Design and Streamlined Conditionality in Recent Low-Income Country Programs. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
An analysis of recent programs in low-income countries, covering countries with continuous program engagement with the IMF throughout the period 2007-09, shows that program design has been adapted to provide expanded policy space in response to the food and fuel price shocks of 2007-08 and to the global financial crisis that followed. The analysis also finds that structural conditionality in Fund-supported programs in low-income countries has become more streamlined, with a dominant focus on public sector resource management and accountability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet